Radiation damage of organism and its correction in conditions of adaptation to highmountain meteorological factors - Білошицький, П.В.; Ключко, О.М.; Онопчук, Ю.М. (Proceedings of National Aviation University (archive), 2022)
Influence of the low doses of radiation on human organism has been registered in conditions of aircraft flies at high altitudes and during space flies. Constant influence of radiation in low doses is also an important factor of meteorological conditions in mountains. The problem of influence of radiation on human organism was at the point of investigation of academician Sirotinin N. N. and researchers of his scientific school who carried out their research work in high mountain conditions at Elbrus medical and biological station (EMBS, National Academy of Science of Ukraine, territory of Russia) till the last years. Obtained results permitted to organize quickly the process of rehabilitation and medical treatment for persons who were irradiated during Chernobyl accident on 1986. In present article are described some mechanisms of radiation influence on organism, oxygen molecules participation in these processes and some methods of medical treatment that were suggested by EMBS researcher basing on these knowledge. The fact of insufficient organism supply by oxygen at high altitudes is considered as important one in some of such methods. In present article some examples from EMBS practice of medical treatment are given as well as numerical results registered during the long years of these effect studies. Obtained results may be useful for the health care of pilots or other groups of people who are influenced by low doses of radiation of different nature during long time.